2014
DOI: 10.1155/2014/637415
|View full text |Cite
|
Sign up to set email alerts
|

rhPDGF-BB Promotes Proliferation and Osteogenic Differentiation of Bone Marrow Stromal Cells from Streptozotocin-Induced Diabetic Rats through ERK Pathway

Abstract: Management of nonunion fracture and massive segmental bone defects in diabetes remains a challenging clinical problem. Bone marrow stromal cells (BMSCs) are crucial for bone remodeling and hold promise for bone regeneration. However, we have showed previously that diabetes can affect the proliferation and osteogenic potential of BMSCs adversely and a strategy to attenuate the impaired functions of BMSCs is required. Platelet-derived growth factor-BB (PDGF-BB) plays an important role in bone formation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Second, although we evaluated the effect of PRP on osteoblast proliferation, we did not evaluate the effect of PRP on osteoblast differentiation. Zhao et al [31] reported that PDGF promotes proliferation and osteogenic differentiation of bone marrow stromal cells via the ERK pathway. Further investigation is required to identify whether FD-PRP also has an osteoblast-differentiating activity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although we evaluated the effect of PRP on osteoblast proliferation, we did not evaluate the effect of PRP on osteoblast differentiation. Zhao et al [31] reported that PDGF promotes proliferation and osteogenic differentiation of bone marrow stromal cells via the ERK pathway. Further investigation is required to identify whether FD-PRP also has an osteoblast-differentiating activity.…”
Section: Discussionmentioning
confidence: 99%
“…ALP staining was performed at day 10. Briefly, the cells were treated with BCIP/NBT solution (Beyotime, Shanghai, China) in the dark, and areas stained purple were regarded as positive [ 36 ]. Moreover, at days 4, 7 and 10, ALP activity was quantitated following the manufacturer’s instructions (Beyotime, China).…”
Section: Methodsmentioning
confidence: 99%
“…Growth factors play an important role in regulating the proliferation of BMSCs, and many growth factors have been found to be involved in this process . However, growth factors are expensive, and the regulatory mechanisms that promote cell proliferation are not clear.…”
Section: Introductionmentioning
confidence: 99%